ECONOMIC ASSESSMENT OF TILLAGE PRACTICES ON PRODUCTIVITY OF COWPEA IN ILE IFE, NIGERIA - Kabiru Alani SHITTU; Omotayo Babawande ADEBOYE; Durodoluwa Joseph OYEDELE; Onyegbula Chike NWOKE; Wasiu Agunbiade LAMIDI; Abdul-salam Mosobalaje MURTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tillage is one of the major threats to soil health which often results into soil physical degradation if not properly manage. Zero tillage was an alternative option from both economic point of view and environmental protection of our invaluable soil resources. The goal of the present scientific paper is to evaluate the response of different tillage systems and evapotranspiration on productivity of cowpea (Vignaunguiculata)in Nigeria. The research was conducted in Obafemi Awolowo University, Ile-Ife Osun State, Nigeria. The research used replicated randomized complete block design with treatments consisting of Zero-tillage (ZT), Reduced tillage (RT), Conventional tillage + Mulch (CT + ML) and Conventional tillage (CT). Exchangeable cations (Ca2+, Mg2+, K+ and Na+) were extracted with neutral solution of 1.0 M NH4OAC.. The K+ and Na+ concentrations in the extract were determined using the flame photometer while Mg2+ and Ca2+ were determined using the atomic absorption. Actual evapotranspiration (ETa) was estimated using the soil water balance approach. Cowpea production on sandy loam top-soil can be optimally produced on Zero tillage system. Considering the profit over two years and the relative energy requirements, ZT system resulted in recording $ 573 profit, which was the highest profit margin among the treatments considered over the two growing seasons, RT ($ 89) had the least value.